Body Weight Estimation in Holstein × Zebu Crossbred Heifers: Comparative Analysis of XGBoost and LightGBM Algorithms - Jose Herrera‐Camacho; Cem Tırınk; Rosa Inés Parra‐Cortés; Lütfi Bayyurt; Rashit Uskenov; Karlygash Omarova; Aizhan Makhanbetova; Kadyrbai Chekirov; Alfonso Juventino Chay‐Canul (Veterinary Medicine and Science, 2025)
ABSTRACT This study evaluates the effectiveness of XGBoost and LightGBM algorithms for estimating the live weight of Holstein×Zebu crossbred heifers. The study compares the performance of both algorithms using a wide range of biometric measurements and tests various hyperparameter settings. The research results show that the XGBoost algorithm provides almost perfect agreement with an R2 value of 0.999 on the training set and high performance with an R2 value of 0.986 on the test set. The LightGBM algorithm also achieved effective results with R2 values of 0.986 and 0.981 on both training and test sets. The machine learning algorithms used in the current study stand out as having the potential to provide a practical and economical solution for live weight estimation in livestock enterprises and especially for herd management applications in rural areas through input variables such as body measurements, milk yield, etc. However, the obtained results in the current study reveal the potential of machine learning algorithms for live weight estimation in the livestock sector and indicate that advanced research is needed for the optimisation of these algorithms.